2010
DOI: 10.1152/ajpheart.00942.2009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urotensin-II infusion induces diastolic dysfunction and enhances collagen production in rats

Abstract: The vasoactive peptide urotensin-II (U-II) is likely to play a key causal role in cardiac remodeling that ultimately leads to heart failure. Its contribution, specifically to the development of diastolic dysfunction and the downstream intracellular signaling, however, remains unresolved. This study interrogates the effect of chronic U-II infusion in normal rats on cardiac structure and function. The contribution of Rho kinase (ROCK) signaling to these pathophysiological changes is evaluated in cell culture stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…It is another effective vasoconstrictor, like ET-1. Recent studies show that U-II could play a fundamental role in cardiovascular remodeling and fibrosis, renal fibrosis, hepatic fibrosis, and in part of the fibrotic process [8,9]. Our investigation revealed that U-II levels are higher in patients with systemic sclerosis (SSc), especially in diffuse fibrotic patients, in contrast to the control group.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…It is another effective vasoconstrictor, like ET-1. Recent studies show that U-II could play a fundamental role in cardiovascular remodeling and fibrosis, renal fibrosis, hepatic fibrosis, and in part of the fibrotic process [8,9]. Our investigation revealed that U-II levels are higher in patients with systemic sclerosis (SSc), especially in diffuse fibrotic patients, in contrast to the control group.…”
Section: Introductionmentioning
confidence: 61%
“…The mechanism of fibrosis remains elusive, and in the treatment of PF, current therapies such as immunosuppressives and steroids are not sufficient [4]. Some cytokines and chemokines, such as TGF-β, connective tissue growth factor, fibroblast growth factor, plateletderived growth factor, insulin-like growth factor (IGF), interleukins (IL-1, IL-10, IL-12, IL-17, IL-4, IL-13), interferon gamma, IGF-1, GM-CSF, tumor necrosis factor-alpha, and ET-1 have been investigated in recent studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Because of the limited treatment alternatives and uncertain pathogenesis, this study was designed to investigate possible therapy alternatives of PF.…”
Section: Discussionmentioning
confidence: 99%
“…The doses of UII used in the current study were based on a previous report [14] and our own experiment. We used two doses of UII: 2.7 µg/kg/h (as low dose) and 5.4 µg/kg/h (as high dose).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac sections, stained with picrosirius red for matrix deposition, [49] were scanned (Aperio, Aperio Technologies Inc., Vista, CA) for analysis. Picrosirius red-stained matrix deposition from the whole LV myocardium, excluding perivascular fibrosis was selected for its intensity, and the proportional area was calculated using a preset algorithm for picrosirius red stain intensity.…”
Section: Methodsmentioning
confidence: 99%